(untitled) (Research, Society and Development, 2021)
A Brazilian public policy on education aimed at promoting local development are the Federal Institutes of Education, Science and Technology (IF’s), which have a decentralized organization and located in several municipalities, including those with a population of less than 10,000 inhabitants. This decentralized structure - multicampi - and the clear definition of the geographical scope of the FIs emphasized the commitment to intervene in their respective locations and regions, through the creation of technical and technological solutions that lead to sustainable development with social inclusion. Therefore, understanding whether the Federal Institutes positively affect local economic development allows us to converge efforts to improve this relationship. This allows for the elaboration of the following question: Does the establishment of Federal Institutes influence local development? In order to answer this question, a clustering of municipalities was carried out using development indicators collected in 2008 and, subsequently, a qualitative analysis between two cities, using indicators collected in 2016, headquarter and non-headquarters of Federal Institutes. The result suggests that the influence of the Federal Institutes can be observed more prominently in municipalities with a lower population concentration, as well as, with more emphasis on education indicators, followed by work and income.